Agricultural Productivity and Multidimensional Poverty Reduction in Colombia: An Analysis of Coffee, Plantain, and Corn Crops - Jaime Andrés Betancourt; Gloria Yaneth Florez-Yepes; Yeison Alberto Garcés-Gómez (Earth)
This article presents the correlation between the Multidimensional Poverty Index (MPI) and the area planted, production in tons, and productive yield for various crops in Colombia from 2018 to 2021. The aim of this study is to determine the relationship between agricultural productivity and multidimensional poverty in Colombia, focusing on the cultivation of coffee, plantain, and corn. The methodology employed included a literature review through a bibliometric analysis to understand the relationships between the MPI and agricultural production. In the second stage, the agricultural sector statistics for the years 2018 to 2021 and the MPI by regions and departments of Colombia during the same period was systematized. Finally, a quantitative statistical analysis was conducted to establish the correlation of the MPI with the area planted, production in tons, and productive yield for coffee, plantain, and corn crops in Colombia. The MPI identifies those who are deprived in 50% or more of the index’s dimensions as living in extreme poverty. The results show that higher productive yields in the crops analyzed correspond to a lower MPI. Coffee crops have an MPI below 50%; plantain crops have an MPI between 20% and 50%, and for mechanized corn crops, the data show an MPI between 20% and 30%. This demonstrates that coffee, plantain, and corn crops represent an alternative for reducing the MPI in Colombia.